Comparative analysis of rhizosphere microbial communities in monoculture and mixed oak–pine forests: structural and functional insights - Liang Qiao; Zhuizhui Guan; Fangfang Ren; Tianxiao Ma (Frontiers in Microbiology)
The ecological significance of rhizosphere microbiomes in forest ecosystems is increasingly recognized. This study provides comparative analysis of microbial communities in Pinus massoniana-Quercus acutissima mixed forests versus monoculture systems. Mixed stands exhibited superior rhizosphere nutrient conditions and supported more diverse microbial populations, particularly with respect to Proteobacteria, Actinobacteria, and Basidiomycota. Principal component analysis revealed clear separation between rhizosphere and non-rhizosphere soil communities, as well as distinct clustering patterns between mixed and pure forest types. The functional analysis revealed conserved metabolic pathways across forest stands, with bacterial metabolic processes and fungal saprophytic functions representing dominant community roles. Network topology analysis demonstrated enhanced connectivity in mixed forest rhizosphere systems, featuring Proteobacteria, Acidobacteria, and Actinobacteria as bacterial network hubs, while Basidiomycota emerged as central fungal network components. Environmental drivers exhibited differential influences, with bacterial assemblages responding primarily to soil pH, organic carbon content, and phosphorus availability, whereas fungal communities showed stronger associations with organic carbon and potassium levels. These findings collectively demonstrate that mixed-species plantations foster robust microbial networks through microenvironmental regulation, offering valuable insights for sustainable forest management practices.